The Correlation Between Visual Learning Style and Students’ Interest in Islamic Religious and Character Education - Fadli Fadli; Uswatun Khasanah; Zahra Rahmatika (MAN 4 Kota Pekanbaru, 2026)
This study aims to analyze the relationship between visual learning style and students’ interest in Islamic Religious and Character Education among tenth-grade students at SMA Negeri 17 Bandar Lampung. It was hypothesized that students with a stronger visual learning style would demonstrate higher interest in learning. The research employed a quantitative correlational design using the ex-post facto method. The population consisted of 120 students, with 54 selected as the sample. Data were collected through a Likert-scale questionnaire tested for validity and reliability. Cronbach’s Alpha values were 0.769 for visual learning style and 0.716 for learning interest, indicating reliable instruments. Data analysis included prerequisite tests, correlation, and simple regression. Results showed a positive and significant relationship, with a correlation coefficient of 0.461 and significance value of 0.010. The coefficient of determination of 0.212 indicates that visual learning style contributes 21.2% to students’ learning interest in Islamic Religious and Character Education context.